Transformation of the Forestry Partnership in the Java Forest: A Study of Community Institutions Lancar Jaya after the Designation of Forest Areas with Special Management - Etrin Herabadi Sunjaya; Hariadi Kartodihardjo; Noer Fauzi Rachman (Sodality: Jurnal Sosiologi Pedesaan, 2024)
The Forest Village Community Institution (LMDH Lancar Jaya) is formed to carry out forestry partnerships in forest areas managed by Perum Perhutani. Along with the designation of this forest area as Forest Areas with Special Management (KHDPK), this institution and its forestry partnerships must be transformed. This study analyzes the timeline and performance of forest village community institutions to describe potential factors for the readiness of partnership transformation. Two theoretical approaches were used in this research: Situation-Structure-Behavior-Performance developed by Schmid (1987; 2004) and Jones’ organizational capacity to produce value (Jones, 2013). The method used was qualitative descriptive, timeline, and content analyses. Research data and information were collected through in-depth interviews and document analysis. This study concludes that the performance of LMDH Lancar Jaya is efficient as an independent and active institution. This performance is driven by significant capital. Good social capital is a strong network of trust in management, solid stakeholder relationships, the ability to choose institutional alternatives that suit their characteristics, minimal transaction costs, and the ability to provide market certainty with interlock transactions. This article recommends the necessary conditions for the transformation of a legal business entity by maximizing inputs for investment capacity in the form of capital, raw materials, human resources, business knowledge, and customers, which is supported by input conversion, administrative fulfillment, and cooperative facilitation of transformation.